Trade unions, labour governance and economic upgradation in value chains: Framing intervention amidst emerging human rights due diligence frameworks - Rohan Dominic Mathews (International Labour Organization (ILO), 2024)
The paper examines possible mechanisms for trade union engagement in global value chains, especially in the context of emerging human rights due diligence frameworks. By examining existing literature on value chain analysis, trade policy, and governance mechanisms, the paper tries to generate a discussion on possible methodologies and knowledge gaps on trade union intervention and decent work in global value chains. The paper examines economic and social upgradation pathways based on available knowledge on skills, labour processes, job profiles and wages. It seeks to open discussions on how global governance forms like national legislation, legal systems and courts, framework agreements, trade agreements, multilateral governance, international human rights and labour conventions can converge with a deeper understanding of economic processes and logics of production and value-addition in GVCs. The paper seeks to position trade unions as effective agents for knowledge-generation and compliance monitoring when it comes to due diligence.
Keywords: 330